Concordance of two sputum smear microscopy for diagnosis of presumptive pulmonary tuberculosis in a tertiary care hospital - Pala, Star; Lynrah, Kyrshan G. (International Journal Of Community Medicine And Public Health, 2017)
Background: Under revised National tuberculosis control program two sputum samples are to be collected for diagnosis of presumptive pulmonary tuberculosis case. The objective of this study is to find the concordance of both sputum smear microscopy samples at a tertiary care hospital. Methods: Hospital based record was collected from designated microscopy center laboratory register. The data collected were from January 2015 to November 2016. Results: A total of 2117 paired of sputum sample were collected for the year 2015-16 in one of the DMC of a tertiary care hospital. A total of 183 patient (at least one sputum sample) were positive (8.64%) and 1934 were both negative. Among the positive sample concordance for both spot and morning samples were 89% (163/183) and discordance where spot sample positive and morning sample negative was 4.91% (9/183) and where spot sample negative and morning sample positive was 6.01% (11/183). Overall discordance between spot and morning samples were only 0.94% (20/2117). Conclusions: There is a good concordance of two sputum samples. Discordance of two sputum samples were <1% in a tertiary care hospital. One sample may be sufficient for operational purpose for diagnosis of pulmonary Tb. But to have a robust recommendation a RCT will be required to see the extent of discordance by ruling out bias in sputum smear examination.